2002
DOI: 10.1046/j.1460-9568.2002.01966.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional glycine receptors are expressed by postnatal nestin‐positive neural stem/progenitor cells

Abstract: Multipotent neural stem and progenitor cells (NS/PCs) are well-established cell subpopulations occurring in the developing, and also in the mature mammalian nervous systems. Trophic and transcription factors are currently the main signals known to influence the development and the commitment of NS/PCs and their progeny. However, recent studies suggest that neurotransmitters could also contribute to neural development. In that respect, rodent-cultured embryonic NS/PCs have been reported to express functional ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
40
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 36 publications
6
40
0
Order By: Relevance
“…Indeed, the expression of NKCC or KCC is critical for neurons to make such a decision. A high level expression of NKCC is often seen in developing neurons in which glycine and GABA produce an excitatory response [41,42]. Our study indicates that NKCC is predominantly expressed in the OPL of salamander retinas, consistent with previous studies in adult mammalian retinas [17,18].…”
Section: New Information For Glycine Receptor Subtypessupporting
confidence: 91%
“…Indeed, the expression of NKCC or KCC is critical for neurons to make such a decision. A high level expression of NKCC is often seen in developing neurons in which glycine and GABA produce an excitatory response [41,42]. Our study indicates that NKCC is predominantly expressed in the OPL of salamander retinas, consistent with previous studies in adult mammalian retinas [17,18].…”
Section: New Information For Glycine Receptor Subtypessupporting
confidence: 91%
“…Consistent with these findings, we observed that, in these multipotent progenitor cells, GlyR subunits forms functional chloride channels gated by glycine and blocked by the GlyR antagonists strychnine and picrotoxin (Nguyen et al, 2002).…”
Section: Focus On a Newcomer: Glycine Receptors In Perinatal Cns Precsupporting
confidence: 86%
“…Using the classical neurosphere culture model from early postnatal striatum , we also demonstrated the expression of GlyR ␣1-, ␣2-and ␤ genes, and could detect GlyR␣ subunit proteins in multipotent nestin-expressing stem/progenitor cells (Nguyen et al, 2002). Consistent with these findings, we observed that, in these multipotent progenitor cells, GlyR subunits forms functional chloride channels gated by glycine and blocked by the GlyR antagonists strychnine and picrotoxin (Nguyen et al, 2002).…”
Section: Focus On a Newcomer: Glycine Receptors In Perinatal Cns Precsupporting
confidence: 75%
See 1 more Smart Citation
“…31 During neurogenesis, extrasynaptic GlyRs and their ligands are present in the forebrain 32,33 as well as in neurogenic regions of the postnatal brain. [34][35][36][37] However, we have limited information about their physiological role in this specific context (reviewed in Avila et al…”
mentioning
confidence: 99%